Challenges of adopting sustainable technologies in e-waste management at Agbogbloshie, Ghana - Selase Kofi Adanu; Shine Francis Gbedemah; Mawutor Komla Attah (Heliyon, 2020)
The study investigated why sustainable technologies are not used to collect, dismantle and sell e-waste at Agbogbloshie given the risk of injury and extensive environmental pollution associated with handling of electronic waste. The study objectives were to examine the nature of technologies adopted to manage e-waste, assess challenges faced in adopting sustainable technologies; determine the missing links between formal and informal e-waste workers. Research questions were; what is the current level of technology adopted to manage e-waste and challenges limiting the adoption of sustainable technologies; and what are the missing links between the formal and informal sectors that limit adoption of sustainable e-waste management strategies. Data collection involved use of questionnaire to gather data on technologies used for e-waste management, challenges faced in using such technologies and what the workers consider as solutions to sustainable e-waste management. Field observations helped to explain waste management operations and questionnaire responses were analyzed using descriptive statistics. Study results show most of the e-waste workers are youthful and not much educated. The use of unsustainable technologies to manage e-waste has contributed to physical injuries to workers and pollution of the environment. A major challenge limiting the use of sustainable technologies is lack of financial resources to acquire modern equipment despite the laborious nature of the work. The paper concludes that sustainable solutions to electronic waste management requires support from government to subsidize the cost of sustainable technologies in e-waste management.